Energy dependence of mass, charge, isotopic, and energy distributions in neutron-induced fission of [235]U and [239]Pu; Physical Review C; Vol. 93, iss. 5 - Pasca H.; Andreev A. V.; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Kim Yu. (2016, 2016)
Title screen